2020
DOI: 10.1093/rheumatology/keaa460
|View full text |Cite
|
Sign up to set email alerts
|

Elevated serum level of hepatocyte growth factor predicts development of new syndesmophytes in men with ankylosing spondylitis

Abstract: Objectives To study baseline serum hepatocyte growth factor (s-HGF) as a predictor of spinal radiographic progression overall and by sex and to analyse factors correlated to changes in s-HGF in patients with AS. Methods At baseline and the 5-year follow-up, s-HGF was analysed with ELISA. Spinal radiographs were graded according to modified Stoke Ankylosing Spondylitis Spinal Score. Radiographic progression was defined as ≥2 m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 43 publications
0
1
0
Order By: Relevance
“…Moreover, HGF was positively associated with risk factors for osteoproliferation, including age, CRP, and smoking [ 38 ]. Another prospective cohort study demonstrated that elevated s-HGF levels were associated with the development of new syndesmophytes in men with AS [ 37 ].…”
Section: Miscellaneous Biomarkersmentioning
confidence: 99%
“…Moreover, HGF was positively associated with risk factors for osteoproliferation, including age, CRP, and smoking [ 38 ]. Another prospective cohort study demonstrated that elevated s-HGF levels were associated with the development of new syndesmophytes in men with AS [ 37 ].…”
Section: Miscellaneous Biomarkersmentioning
confidence: 99%